Developing Mathematical Literacy-Based Teaching Materials with the Assistance of the Lumi Platform for Middle School Ratio Materials - Lidia Salasa; Vita Istihapsari (JNPM (Jurnal Nasional Pendidikan Matematika), 2026)
Mathematics learning in junior high schools is still procedural which causes low mathematical literacy of students. This study developed mathematical literacy-based teaching materials assisted by the Lumi platform for grade VII semester 1 and assessed its validity and practicality using the Research and Development (R&D) approach based on the AADIE model. The subjects of the study were grade VII students of Muhammadiyah 9 Yogyakarta Junior High School. The data were obtained from expert review questionnaires and practicality assessments administered to teachers and learners, which were quantitatively analyzed using a Likert scale. The results showed that the teaching materials were very valid 94.85% from material experts, 97.5% from media experts, very practical 89.06% from teachers, and practical 79.13% from students so that the teaching materials were suitable for use in junior high school mathematics learning.